2008
DOI: 10.1097/mlg.0b013e3181585428
|View full text |Cite
|
Sign up to set email alerts
|

Can Intratympanic Dexamethasone Added to Systemic Steroids Improve Hearing Outcome in Patients With Sudden Deafness?

Abstract: The addition of ITD to systemic steroids did not result in significant improvements in the treatment of idiopathic sudden HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
2
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 18 publications
4
118
2
11
Order By: Relevance
“…152 Another study combining oral and IT corticosteroids did not show a difference in hearing recovery compared with corticosteroids alone. 153 A recent study proposed IT treatment as the sole initial treatment. 154 The protocol consisted of early injections for 3 consecutive days, with only 3 of 34 patients failing to improve.…”
Section: Intratympanic Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…152 Another study combining oral and IT corticosteroids did not show a difference in hearing recovery compared with corticosteroids alone. 153 A recent study proposed IT treatment as the sole initial treatment. 154 The protocol consisted of early injections for 3 consecutive days, with only 3 of 34 patients failing to improve.…”
Section: Intratympanic Corticosteroidsmentioning
confidence: 99%
“…9,153,155,157,[198][199][200][201][202] One critical problem in the individual trials is how an improvement in hearing was defined. Most authors used a 10-dB HL improvement in the PTA or an improvement in WRS of 15% or 20% as indicative of successful treatment.…”
Section: Supporting Textmentioning
confidence: 99%
“…In a randomized, prospective study, Arslan et al [20] reported that SS+IT methylprednisolone (0.5 mL, every other day, 5 injections) may increase the healing ratios. On the other hand, in a study of Ahn et al [21] comparing 0.3 mL IT dexamethasone application on1, 3, and 5 days concomitant with SS with only SS treatment, they reported that ITS treatment concomitant with SS does not cause significant improvement. In a prospective, randomized, controlled trial of Park et al [22] , IT dexamethasone treatment concomitant with SS was compared with ITS administration after SS treatment and was …”
Section: Discussionmentioning
confidence: 99%
“…However, a combination of a high-dose prednisone taper with IT steroids resulted in partial or complete hearing recovery in 14 of 16 patients [15]. Another study combining oral and IT corticosteroids did not show a difference in hearing recovery compared with corticosteroids alone [16]. A recent study proposed IT treatment as the sole initial treatment [17].…”
Section: Discussionmentioning
confidence: 99%